High-performance PTFE nanocomposites based on halloysite nanotubes. (December 2017) - Cheng, Zhi-Lin; Chang, Xing-Yu; Liu, Zan; Qin, Dun-Zhong; Zhu, Ai-Ping
Abstract: Halloysite nanotubes (HNTs)/polytetrafluoroethylene (PTFE) nanocomposites were prepared by the cold compression moulding method. The effects of addition of HNTs (HNTs 'filling') on the performances of PTFE were explored using X-ray diffraction, Fourier Transform infrared spectroscopy, scanning electron microscopy and thermogravimetric analysis which showed that HNTs were well dispersed in the PTFE matrix by means of physical mixing at lower contents of 2–5 wt.%; the introduction of HNTs into PTFE could improve the heat stability of the PTFE. Furthermore, the mechanical and tribological performances of the nanocomposites were measured to examine the filling effect. The tensile strength of the HNTs/PTFE nanocomposites at 2–5 wt.% HNTs content increased by 3.5% while their wear rates decreased by 55–90% relative to pure PTFE, clear proof of the filling effect of HNTs with a high aspect ratio.